2019
DOI: 10.1007/s00423-019-01751-8
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and anatomy of parathyroid glands: a meta-analysis with implications for parathyroid surgery

Abstract: Purpose The anatomy of parathyroid glands (PTG) is highly variable in the population. The aim of this study was to conduct a systematic analysis on the prevalence and location of PTG in healthy and hyperparathyroidism (HPT) patients. Methods An extensive search of the major electronic databases was conducted to identify all studies that reported relevant data on the number of PTG per patient and location of PTG. The data was extracted from the eligible studies and poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
73
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 37 publications
1
73
0
15
Order By: Relevance
“…In the majority of cases, four PGs are present, nevertheless, there are individuals either with a less or excessive number of PGs (even up to twelve glands) [24]. The results of a recent meta-analysis, which involved 26 studies and 7005 patients, showed that 81.4% of patients had four PGs [25]. Regarding the geographical location, the results of the studies in North and South America revealed a smaller number of patients with four PGs compared to Europe.…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of cases, four PGs are present, nevertheless, there are individuals either with a less or excessive number of PGs (even up to twelve glands) [24]. The results of a recent meta-analysis, which involved 26 studies and 7005 patients, showed that 81.4% of patients had four PGs [25]. Regarding the geographical location, the results of the studies in North and South America revealed a smaller number of patients with four PGs compared to Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical failure is mainly due to the di culty of resecting all parathyroid glands, especially because of the existence of supernumerary (more than 4) and ectopic parathyroid glands. The incidence of ectopic and supernumerary glands in patients with end-stage renal disease has been reported to be 17.5-39.3% and 6.3-37%, respectively [7][8][9]. Therefore, preoperative imaging and accurate localization are critical to a successful operation.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical failure is mainly due to the difficulty to resect all parathyroid glands especially because of the existence of supernumerary (more than 4) and ectopic parathyroid glands. It is reported that the incidences of ectopic and supernumerary glands reported in patients with end-stage kidney disease are 17.5-39.3% and 6.3-37%, respectively [7][8][9].Therefore, preoperative imaging and accurate localization is critical to a successful operation.…”
Section: Introductionmentioning
confidence: 99%